FORMULASI DAN UJI SIFAT FISIK SEDIAAN GEL EKSTRAK ETANOLIK GANGGANG HIJAU (Ulva Lactuca LINN.) - Emelda, Emelda; Septiawan, Azizah Nada; Pratiwi, Dinda Ayu; Prasetya, Didik Yuni (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
One of the skin diseases that are often experienced by people is acne. The bacteria found in acne are P. acnes, S. aureus, and S. epidermidis. The preparation was chosen in this formulation because it is more practical and durable in storage. Gel preparations were chosen because it dry easily, can form a film layer that is easy to wash, and gives a cool feeling to the skin. Physical stability tests need to be carried out to ensure the quality, safety, and usefulness of the gel so that it meets the expected specifications and is stable in storage. This study aims to make a gel formulation and determine the physical properties of green algae Ethanolic extract gel. The optimum gel formula is determined based on variations in the concentration of Hydroxypropyl methylcellulose. The Gel that meets the criteria of homogeneity, consistency, pH , and dispersibility is determined as the optimum formula. The physical stability of the optimum formula was tested by organoleptic, homogeneity, pH test, spreadability test, and viscosity test. The gel that met the acceptance criteria was green algae ethanolic extract gel with a concentration of 3% HPMC so that it was determined as the optimum formula.